The evolutionary argument against naturalism: a Wittgensteinian response - DeVito, Michael; McNabb, Tyler (International Journal for Philosophy of Religion, 2022)
In this essay, we put forth a novel solution to Plantinga’s Evolutionary Argument Against Naturalism, utilizing recent work done by Duncan Pritchard on radical skepticism. Key to the success of Plantinga’s argument is the doubting of the reliability of one’s cognitive faculties. We argue (viz. Pritchard and Wittgenstein) that the reliability of one’s cognitive faculties constitutes a hinge commitment, thus is exempt from rational evaluation. In turn, the naturalist who endorses hinge epistemology can deny the key premise in Plantinga’s argument and avoid the dilemma posed on belief in the conjunction of naturalism and evolution.